Interfacing a Personal Glucose Meter with Cell-Free Protein Synthesis for Rapid Analysis of Amino Acids - Jang, Yeon Jae; Lee, Kyung Ho; Yoo, Tae Hyeon; Kim, Dong Myung (Analytical Chemistry, 2019)
We developed a method to analyze amino acids using a personal glucose meter (PGM). In this method, the principles of protein biosynthesis were interfaced with the sensing mechanism of a PGM to enable simple and ubiquitous measurement of amino acids. A reaction mixture for cell-free protein synthesis was designed to synthesize a bacterial invertase in response to exogenous addition of a specific amino acid. The invertase synthesized upon addition of an assay sample containing the amino acid of interest was used to convert sucrose into glucose, which was detected using a PGM. The titers of the amino acid in assay samples were precisely represented by the readouts of a PGM. In addition to the convenience provided by use of a PGM, the accuracy and reproducibility of this method were comparable to those of standard high-performance liquid chromatography based methods.
Keywords: Cell free protein synthesis; Protein biosynthesis; Rapid analysis; Reaction mixture; Reproducibilities; Sensing mechanism